Progress towards the mandatory code for polar shipping - Julia Jabour (2014)
A mandatory international code for safer shipping, which in turn will help protect vulnerable marine environments in polar waters, is imminent. It began life as recommendatory guidelines from the International Maritime Organization (IMO) to apply only to ships in Arctic waters. But a request from the Antarctic Treaty Consultative Parties prompted the expansion of these guidelines into mandatory rules for shipping in both polar regions. Choices for the form and scope of the code included, among others, the adoption of a separate convention or the addition of annexes to supplement the International Convention for the Prevention of Marine Pollution from Ships (MARPOL) and the International Convention for the Safety of Life at Sea (SOLAS). The technical difficulties associated with a mandatory code applying to ships servicing the Arctic or the Antarctic or both have largely been overcome and a riskbased code is about to be adopted and applied, in the first instance, to SOLAS-rated vessels.